The Impact of Linguistik and Literacy Futurology on Islamic Early Childhood Education Curriculum - Wildan Aji Saputra; Entoh Tohani; Rahayu Fuji Astuti; Siti Amironah (Journal of Educational Studies, 2025)
The rapid transformation of the modern world requires early childhood education (ECE) to go beyond basic value transmission by equipping children with visionary and creative thinking skills. This study aims to examine the influence of integrating language and literature-based futurology into the development of an Islamic early childhood education curriculum as a projection of future-oriented education. A quantitative approach with a quasi-experimental design was employed, involving two groups: experimental and control, each comprising 20 children aged 5–6 years in Medan Sunggal District. Data were collected through pretests, posttests, structured observations, and teacher questionnaires, and analyzed using independent t-tests. The results indicate that the experimental group experienced significant improvements in language development, imagination, and Islamic spiritual values compared to the control group (p < 0.05). Additionally, the study found increased empathy and social interaction among children in the experimental group, although this was not a primary research focus. These findings suggest that an Islamic ECE curriculum integrated with language and literature-based futurology can serve as a strategic innovation in addressing the challenges of 21st-century education.